Myeloid-Derived Suppressor Cells Are Increased in Lung Transplant Recipients and Regulated by Immunosuppressive Therapy - Iglesias-Escudero, María; Segundo, David San; Merino-Fernandez, David; Mora-Cuesta, Victor M.; Lamadrid, Patricia; Alonso-Peña, Marta; Raso, Sandra; Iturbe, David; Fernandez-Rozas, Sonia; Cifrian, Jose; López-Hoyos, Marcos (Frontiers in Immunology, 2022)
Lung transplantation remains as a primary treatment for end-stage lung diseases. Although remarkable improvement has been achieved due to the immunosuppressive protocols, long-term survival for lung transplant recipients (LTR) is still limited. In the last few decades, an increasing interest has grown in the study of dysregulation of immune mechanisms underlying allograft failure. In this regard, myeloid-derived suppressor cells (MDSCs) could play an important role in the promotion of graft tolerance due to their immune regulatory function. Here, we describe for the first time circulating subsets MDSCs from LTR at several time points and we evaluate the relationship of MDSCs with sort-term lung transplant outcomes. Although no effect of MDSCs subsets on short-term clinical events was observed, our results determine that Mo-MDSCs frequencies are increased after acute cellular rejection (ACR), suggesting a possible role for Mo-MDSCs in the development of chronic lung allograft dysfunction (CLAD). Therefore, whether MDSCs subsets play a role as biomarkers of chronic rejection remains unknown and requires further investigations. Also, the effects of the different immunosuppressive treatments on these subpopulations remain under research and further studies are needed to establish to what extend MDSCs immune modulation could be responsible for allograft acceptance.